BUNYI KONSONAN BAHASA INDONESIA DAN BAHASA MANDARIN: ANALISIS KONTRASTIF - Yuk Ting (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2011)
Today, there are many people start to learn Chinese language, one of the most important language in the world. The pronounciation is unique, especially the consonants. They have some contrast in the consonants. First, is between retroflex and alveolar sounds, like zh[tʂ]-z[ts]; ch[ tʂ’]-c[ts’]; sh[ʂ]-s[s]. Second, is between the aspirated and not aspirated sounds, like b[p]-p[p’]; d[t]-t[t’]; g[k]-k[k’]; j[tɕ]-q[tɕ’]; zh[tʂ]-ch[ tʂ’] and z[ts]-c[ts’]. Many Indonesian people can speak Chinese fluently, but some of them are really hard to pronounce the retroflex sounds and the aspirated sounds. Because Indonesian language doesn’t have retroflex sounds or aspirated sounds. It doesn’t mean that Indonesian peoples do not able to speak Chinese with the right pronounciation. This academic journal will compare the consonants of Chinese language and Indonesian language, find out the equal and the difference in it. By doing such comparison, we can find the way to solve the problem of Chinese language pronounciation, especially in consonants.